A method for regulating the morphology and size of catechol-based resin micro-nanospheres

By using tannin as a crosslinker to react with catechol and formaldehyde, the amount of tannin is adjusted to control the particle size of the phenolic resin microspheres, solving the problem of difficult particle size regulation in the prior art, and achieving the regulation and application potential of particle size in the range of 300 to 800 nm.

CN115894976BActive Publication Date: 2025-04-29QILU UNIVERSITY OF TECHNOLOGY (SHANDONG ACADEMY OF SCIENCES)
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202211214028.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-09-30
Publication Date
2025-04-29
Estimated Expiration
2042-09-30

AI Technical Summary

Technical Problem

The prior art is difficult to regulate the particle size of phenolic resin microspheres through simple and green methods, and the particle size regulation range is limited, which affects its application.

Method used

Tannic acid is used as a crosslinking agent to react with catechol and formaldehyde. By adjusting the amount of tannin acid, the particle size of the resin ball is adjusted to achieve regulation of the particle size in the range of 300-800 nm.

Benefits of technology

The particle size of the phenolic resin ball was successfully reduced, and the particle size was adjusted widely by adjusting the amount of tannin added, which improved the application potential of the resin ball.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115894976B_ABST
    Figure CN115894976B_ABST
Patent Text Reader

Abstract

The present invention belongs to the field of advanced material technology, and relates to the preparation of biomass-based nanomaterials, and specifically to a method for regulating the morphology and size of catechol-based resin micro-nanospheres. Catechol, tannic acid, and ammonia water are added to a mixed solution of ethanol and water and mixed evenly, and formaldehyde is added to carry out a solvent thermal reaction to obtain catechol-based resin micro-nanospheres; the size of the catechol-based resin micro-nanospheres is adjusted by adjusting the amount of tannic acid added. The method of the present invention can further reduce the particle size of phenolic resin spheres, and can adjust the particle size of phenolic resin spheres in a wide range by adjusting parameters, and can also achieve a high amount of silver nanoparticle loading.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of advanced materials, relates to the preparation of biomass-based nanomaterials, and specifically to a method for regulating the morphology and size of catechol-based resin micro-nanospheres. Background Art

[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.

[0003] Resin micro-nanospheres such as phenol, catechol and resorcinol have attracted extensive attention from scholars because of their good chemical durability, stability and corrosion resistance in complex environments. The physicochemical properties of resin micro-nanospheres are closely related to their size, particle size distribution range, specific surface area, surface roughness and active group content. However, it is still challenging to achieve the regulation of the morphology and size of resin spheres through simple and green steps. In previous studies, tannic acid coating can increase the loading capacity of phenolic resin microspheres on silver nanoparticles. However, the particle size of phenolic resin microspheres formed by tannic acid coating is all in the micron level, which is relatively large; at the same time, it is impossible to regulate the particle size of phenolic resin microspheres on a large scale, which to some extent affects the application of phenolic resin microspheres. Summary of the invention

[0004] In order to overcome the deficiencies of the prior art, the purpose of the present invention is to provide a method for regulating the morphology and size of catechol-based resin micro-nanospheres, which can further reduce the particle size of the phenolic resin spheres and adjust the particle size of the phenolic resin spheres over a wide range by adjusting parameters.

[0005] In order to achieve the above object, the technical solution of the present invention is:

[0006] On the one hand, a method for preparing catechol-based resin micro-nanospheres is provided, wherein catechol, tannic acid, and ammonia water are added to a mixed solution of ethanol and water, mixed evenly, and formaldehyde is added and subjected to solvent thermal reaction to obtain the micro-nanospheres.

[0007] In order to adjust the particle size of catechol-based resin micro-nanospheres, the present invention first uses lignin as a cross-linking agent to react with catechol and formaldehyde. However, it is found that when lignin is used as a cross-linking agent, the yield of the resin spheres obtained is extremely low, and the ratio of lignin doping can only reach 30wt.%. With the continued addition of lignin, the activity of the reaction deteriorates, and the yield of the resin spheres is further reduced, or even does not react. Therefore, doping lignin and utilizing catechol to react with formaldehyde cannot obtain resin spheres with high yield and controllable morphology and size. For this reason, the present invention selects tannic acid with higher reaction activity as the raw material of the cross-linking reaction, and further reacts with catechol and formaldehyde. This method can not only obtain resin spheres with a smaller high yield in size, but also can achieve the regulation of the particle size of the resin spheres by adjusting the ratio of adding tannic acid.

[0008] On the other hand, a method for regulating the morphology and size of catechol-based resin micro-nanospheres includes the above-mentioned preparation method, and the size of the catechol-based resin micro-nanospheres is regulated by adjusting the amount of tannic acid added.

[0009] Studies have shown that the present invention can achieve the regulation of the size of catechol-based resin micro-nanospheres within the range of 300 to 800 nm by adjusting the amount of tannic acid added.

[0010] In a third aspect, a method for preparing catechol-based resin micro-nanospheres loaded with silver nanoparticles includes the above-mentioned method for preparing catechol-based resin micro-nanospheres, adding the prepared catechol-based resin micro-nanospheres into a silver ammonia solution and stirring at room temperature to obtain the product.

[0011] The catechol-based resin micro-nanospheres obtained by the invention not only have smaller sizes but also can carry more silver particles.

[0012] In a fourth aspect, a use of the catechol-based resin micro-nanospheres obtained by the preparation method of the catechol-based resin micro-nanospheres as a carrier of precious metal nanomaterials.

[0013] The beneficial effects of the present invention are:

[0014] 1. The tannic acid used in the present invention is a natural water-soluble plant polyphenol, which is the second largest phenolic biopolymer on earth, is cheap and widely available. Therefore, using tannic acid as a cross-linking monomer for the synthesis of resin balls can reduce the use of phenolic chemicals and follow the concept of green environmental protection.

[0015] 2. By controlling the addition ratio of tannic acid, size-controlled phenolic resin nanospheres can be obtained, which is of great significance for expanding its application fields.

[0016] 3. The surface roughness and surface phenolic hydroxyl content of the resin balls synthesized with tannic acid as the cross-linking monomer are improved, which is beneficial for its use as a catalyst carrier. For example, it can significantly increase the loading amount of nanosilver on its surface, making it exhibit higher catalytic activity during the catalytic degradation of dye waste liquid.

[0017] 4. Due to the rich phenolic hydroxyl content of tannic acid, there is a high hydroxyl ionization effect on the surface of the resin balls involved in the synthesis. Therefore, the resin balls have a higher specific surface charge in the solution system and can show excellent solution dispersibility and stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.

[0019] Figure 1 1 is a technical roadmap for the preparation of the embodiments of the present invention, (a) is the preparation route of the traditional phenol-loaded silver microspheres, (b) is the preparation route of the catechol-based micro-nanospheres loaded with silver prepared in the embodiments of the present invention, (c) is a property comparison between the traditional phenol-loaded silver microspheres and the catechol-based micro-nanospheres loaded with silver in the embodiments of the present invention, (d) is a morphology comparison between the traditional phenol microspheres and the catechol-based micro-nanospheres in the embodiments of the present application, (e) is a comparison of the adsorption performance of the traditional phenol-loaded silver microspheres and the catechol-based micro-nanospheres loaded with silver in the embodiments of the present invention, and (f) is a comparison of the reduction and chelation capabilities of the traditional phenol-loaded silver microspheres and the catechol-based micro-nanospheres loaded with silver in the embodiments of the present invention;

[0020] Figure 2 The scanning electron microscope images and particle size distribution diagrams of TA-PFR nanospheres prepared with different tannic acid doping amounts obtained in the examples of the present invention are shown in Figures a and b, respectively, for TA0-PFR in Example 1, TA5-PFR in Example 2, and TA3-PFR in Example 3. 10 -PFR, d is Example 4TA 20 -PFR, e is Example 5TA 40 -PFR, f is Example 6TA 50 -PFR, g is Example 7TA 60 -PFR, h is Example 8TA 80 -PFR;

[0021] Figure 3 is the TA obtained in the embodiment of the present invention 40 -SEM and TEM images of PFR@Ag silver nanospheres, a is the SEM image of Example 1, b is the SEM image of Example 5, c is the TEM image of Example 5, d is the TEM image of Example 5, e is the TEM image of Example 5, and f is the element distribution map of Example 5;

[0022] Figure 4 The PFR@Ag of Example 1 and TA of Example 5 obtained by the present invention 40 -Comparison of silver content in PFR@Ag. DETAILED DESCRIPTION

[0023] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.

[0024] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit exemplary embodiments according to the present invention. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should be understood that when the terms "comprising" and / or "including" are used in this specification, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.

[0025] In view of the problem in previous studies that phenolic resin microspheres with high silver nanoparticle loading have large particle size and are difficult to achieve large-scale regulation, the present invention proposes a method for regulating the morphology and size of catechol-based resin micro-nanospheres.

[0026] A typical embodiment of the present invention provides a method for preparing catechol-based resin micro-nanospheres, wherein catechol, tannic acid, and ammonia water are added to a mixed solution of ethanol and water and mixed evenly, and formaldehyde is added and then subjected to solvent thermal reaction to obtain the micro-nanospheres.

[0027] The present invention shows that when tannic acid is used as a cross-linking agent, on the basis of being able to form resin balls, not only can the size of the obtained resin balls be smaller, but also the particle size of the resin balls can be adjusted by adjusting the proportion of the added tannic acid.

[0028] In some embodiments, the addition ratio of catechol to tannic acid is 1:30 to 550, mol:g. Under the premise that other conditions remain unchanged, tannic acid within this range can better obtain resin balls with smaller sizes, and the size of the resin balls can be easily controlled by adjusting the amount of tannic acid.

[0029] In some embodiments, the uniform mixing method is ultrasonic treatment. Uniform mixing requires a mixing device (such as a stirrer, ultrasonic device) to disturb the material. Since the solvothermal reaction is carried out under closed conditions, the material generally needs to be transported to a high-pressure reactor during the solvothermal reaction. Compared with the stirring mixing method, ultrasonic treatment does not require a stirring rod to be placed in the material, which makes it easier to avoid material loss, thereby better realizing the control of each material in the solvothermal reaction.

[0030] In some embodiments, the volume ratio of ethanol to water is 100:3-5.

[0031] In some embodiments, the temperature of the solvothermal reaction is 100-200° C., and the reaction time is 6-24 h.

[0032] The concentration of the ammonia water is 22-28 wt %. The concentration of commercially available ammonia water is generally about 25 wt % (±1 wt %), and the present invention is recorded as 25 wt %.

[0033] Another embodiment of the present invention provides a method for regulating the morphology and size of catechol-based resin micro-nanospheres, including the preparation method of the above-mentioned catechol-based resin micro-nanospheres, and regulating the size of the catechol-based resin micro-nanospheres by adjusting the amount of tannic acid added.

[0034] In some embodiments, when the added molar amount of catechol is 1 mol, the added amount of tannic acid is adjusted within the range of 30 to 550 g. During the adjustment of the added amount of tannic acid, other conditions except the added amount of tannic acid remain unchanged.

[0035] The third embodiment of the present invention provides a method for preparing catechol-based resin micro-nanospheres loaded with silver nanoparticles, comprising the above-mentioned method for preparing catechol-based resin micro-nanospheres, adding the prepared catechol-based resin micro-nanospheres into a silver ammonia solution and stirring at room temperature to obtain the obtained product.

[0036] Studies have shown that the amount of silver nanoparticles loaded on the catechol-based resin micro-nanospheres prepared by the present invention can be guaranteed to be above 48wt%.

[0037] In some embodiments, the silver ammonia solution is prepared by mixing a low-concentration ammonia solution with a silver nitrate solution until all of the silver nitrate solution is dissolved. The low-concentration ammonia solution of the present invention refers to an ammonia solution with a concentration of less than 20 wt.%, generally 5 to 10 wt.%.

[0038] A fourth embodiment of the present invention provides a method for preparing catechol-based resin micro-nanospheres, and uses the catechol-based resin micro-nanospheres obtained by the method as carriers of precious metal nanomaterials.

[0039] The noble metal nanomaterials include nanomaterials such as gold nanoparticles, platinum nanoparticles and rhodium nanoparticles.

[0040] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in conjunction with specific embodiments.

[0041] Example 1

[0042] Using improved Method for preparing tannic acid doped catechol resin nanospheres (TA0-PFR): Catechol (600 mg, 0.9 mmol) and 25 wt% ammonia solution (0.9 mL, 5 mmol) were added to 120 mL ethanol and 48 mL deionized water, respectively. The mixed solution was ultrasonically treated for 5 minutes. Then 0.84 mL (3.8 mmol) of formaldehyde solution was added to the above solution, and then the mixed solution was transferred to a sealed polytetrafluoroethylene autoclave, reacted at a constant temperature of 160 ° C for 6 hours, and finally washed with water and ethanol for multiple times, collected and dried after centrifugation to obtain TA0-PFR nanospheres, i.e. PFR nanospheres, such as Figure 2 As shown in a.

[0043] The typical synthesis process of PFR@Ag nanospheres is: using silver ammonia solution (Tollens') as the Ag precursor solution, Ag nanoparticles are synthesized on PFR nanospheres. 5wt% ammonia solution is added to 10mg mL -1 The prepared PFR nanospheres (60 mg) were added to the above silver ammonia solution and stirred at room temperature for 4 h. After in situ reduction, they were washed with water and ethanol for multiple times, centrifuged, collected and dried to obtain PFR@Ag nanospheres.

[0044] Example 2

[0045] Using improved Method for preparing tannic acid-doped catechol resin nanospheres (TA5-PFR): Catechol (570 mg, 0.9 mmol), tannic acid (30 mg) and 25 wt% ammonia solution (0.9 mL, 5 mmol) were added to 120 mL ethanol and 48 mL deionized water, respectively. The mixed solution was ultrasonically treated for 5 minutes. Then 0.84 mL (3.8 mmol) of formaldehyde solution was added to the above solution, and then the mixed solution was transferred to a sealed polytetrafluoroethylene autoclave, reacted at a constant temperature of 160 ° C for 6 hours, and finally washed with water and ethanol for multiple times, collected and dried after centrifugation to obtain TA5-PFR nanospheres, such as Figure 2 As shown in b.

[0046] Example 3

[0047] Using improved Preparation of tannic acid-doped catechol resin nanospheres (TA 10-PFR): Catechol (540 mg, 0.9 mmol), tannic acid (60 mg) and 25 wt% ammonia solution (0.9 mL, 5 mmol) were added to 120 mL ethanol and 48 mL deionized water, respectively. The mixed solution was ultrasonically treated for 5 minutes. Then 0.84 mL (3.8 mmol) of formaldehyde solution was added to the above solution, and then the mixed solution was transferred to a sealed polytetrafluoroethylene autoclave, reacted at a constant temperature of 160 ° C for 6 hours, and finally washed with water and ethanol for multiple times, collected and dried after centrifugation to obtain TA 10 -PFR nanospheres, such as Figure 2 As shown in c.

[0048] Example 4

[0049] Using improved Preparation of tannic acid-doped catechol resin nanospheres (TA 20 -PFR): Catechol (480 mg, 0.9 mmol), tannic acid (120 mg) and 25 wt% ammonia solution (0.9 mL, 5 mmol) were added to 120 mL ethanol and 48 mL deionized water, respectively. The mixed solution was ultrasonically treated for 5 minutes. Then 0.84 mL (3.8 mmol) of formaldehyde solution was added to the above solution, and then the mixed solution was transferred to a sealed polytetrafluoroethylene autoclave, reacted at a constant temperature of 160 ° C for 6 hours, and finally washed with water and ethanol for multiple times, collected and dried after centrifugation to obtain TA 20 -PFR nanospheres, such as Figure 2 As shown in d.

[0050] Example 5

[0051] Using improved Preparation of tannic acid-doped catechol resin nanospheres (TA 40 -PFR): Catechol (360 mg, 0.9 mmol), tannic acid (240 mg) and 25 wt% ammonia solution (0.9 mL, 5 mmol) were added to 120 mL ethanol and 48 mL deionized water, respectively. The mixed solution was ultrasonically treated for 5 minutes. Then 0.84 mL (3.8 mmol) of formaldehyde solution was added to the above solution, and then the mixed solution was transferred to a sealed polytetrafluoroethylene autoclave, reacted at a constant temperature of 160 ° C for 6 hours, and finally washed with water and ethanol for multiple times, collected and dried after centrifugation to obtain TA 40 -PFR nanospheres, collected and dried after centrifugation, as Figure 2 As shown in e.

[0052] TA 40 The typical synthesis process of -PFR@Ag nanospheres is: using silver ammonia solution (Tollens') as Ag precursor solution, 40Ag nanoparticles were synthesized on the PFR nanospheres. 5 wt% ammonia solution was added to 10 mg mL -1 30 mL of AgNO3 solution was added until the brown precipitate was completely dissolved to obtain a silver ammonia solution. 40 -PFR nanospheres (60 mg) were added to the above silver ammonia solution and stirred at room temperature for 4 h. After in situ reduction, they were washed with water and ethanol several times, centrifuged, collected and dried to obtain TA 40 -PFR@Ag nanospheres, the synthesis process is as follows Figure 1 shown.

[0053] Example 6

[0054] Using improved Preparation of tannic acid-doped catechol resin nanospheres (TA 50 -PFR): Catechol (300 mg, 0.9 mmol), tannic acid (300 mg) and 25 wt% ammonia solution (0.9 mL, 5 mmol) were added to 120 mL ethanol and 48 mL deionized water, respectively. The mixed solution was ultrasonically treated for 5 minutes. Then 0.84 mL (3.8 mmol) of formaldehyde solution was added to the above solution, and then the mixed solution was transferred to a sealed polytetrafluoroethylene autoclave, reacted at a constant temperature of 160 ° C for 6 hours, and finally washed with water and ethanol for multiple times, collected and dried after centrifugation to obtain TA 50 -PFR nanospheres, such as Figure 2 f.

[0055] Example 7

[0056] Using improved Preparation of tannic acid-doped catechol resin nanospheres (TA 60 -PFR): Catechol (240 mg, 0.9 mmol), tannic acid (360 mg) and 25 wt% ammonia solution (0.9 mL, 5 mmol) were added to 120 mL ethanol and 48 mL deionized water, respectively. The mixed solution was ultrasonically treated for 5 minutes. Then 0.84 mL (3.8 mmol) of formaldehyde solution was added to the above solution, and then the mixed solution was transferred to a sealed polytetrafluoroethylene autoclave, reacted at a constant temperature of 160 ° C for 6 hours, and finally washed with water and ethanol for multiple times, collected and dried after centrifugation to obtain TA 60 -PFR nanospheres, such as Figure 2 As shown in g.

[0057] Example 8

[0058] Using improved Preparation of tannic acid-doped catechol resin nanospheres (TA 80-PFR): Catechol (120 mg, 0.9 mmol), tannic acid (480 mg) and 25 wt% ammonia solution (0.9 mL, 5 mmol) were added to 120 mL ethanol and 48 mL deionized water, respectively. The mixed solution was ultrasonically treated for 5 minutes. Then 0.84 mL (3.8 mmol) of formaldehyde solution was added to the above solution, and then the mixed solution was transferred to a sealed polytetrafluoroethylene autoclave, reacted at a constant temperature of 160 ° C for 6 hours, and finally washed with water and ethanol for multiple times, collected and dried after centrifugation to obtain TA 80 -PFR nanospheres, such as Figure 2 h.

[0059] Depend on Figure 2 The results showed that adding tannic acid could obtain small-sized resin balls, and the size of the resin balls gradually decreased with the addition amount of tannic acid.

[0060] PFR@Ag nanospheres prepared in Example 1 and TA prepared in Example 5 40 -The silver content of PFR@Ag nanospheres is Figure 4 , as shown in Table 1.

[0061] Table 1 Silver content

[0062] sample Element content (mg / kg) wt.% Example 1 384598.46 38.4598 Example 5 484064.67 48.4065

[0063] Table 1 shows that the TA obtained by cross-linking with tannic acid 40 -PFR can increase the loading capacity of silver nanoparticles. Figure 1 It shows that the higher the loading of silver nanoparticles, the 40 -PFR has higher adsorption capacity, reduction capacity and chelation capacity.

[0064] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing catechol-based resin micro-nanospheres, characterized in that: Add catechol, tannic acid and ammonia water to a mixed solution of ethanol and water and mix evenly, add formaldehyde and perform solvent thermal reaction to obtain; The addition ratio of catechol to tannic acid is 1:30-550, mol:g.

2. The method for preparing catechol-based resin micro-nanospheres according to claim 1, characterized in that: The uniform mixing method is ultrasonic treatment.

3. The method for preparing catechol-based resin micro-nanospheres according to claim 1, characterized in that: The volume ratio of ethanol to water is 100:3-5.

4. The method for preparing catechol-based resin micro-nanospheres according to claim 1, characterized in that: The temperature of the solvent thermal reaction is 100-200°C, and the reaction time is 6-24h.

5. A method for regulating the morphology and size of catechol-based resin micro-nanospheres, characterized in that: The invention comprises the method for preparing the catechol-based resin micro-nanospheres according to any one of claims 1 to 4, wherein the size of the catechol-based resin micro-nanospheres is adjusted by adjusting the amount of tannic acid added.

6. The method for regulating the morphology and size of catechol-based resin micro-nanospheres according to claim 5, characterized in that: When the added molar amount of catechol is 1 mol, the added amount of tannic acid is adjusted within the range of 30 to 550 g. During the adjustment of the added amount of tannic acid, other conditions except the added amount of tannic acid remain unchanged.

7. A method for preparing catechol-based resin micro-nanospheres loaded with silver nanoparticles, characterized in that: The invention comprises the preparation method of the catechol-based resin micro-nanospheres according to any one of claims 1 to 4, wherein the prepared catechol-based resin micro-nanospheres are added into a silver ammonia solution and stirred at room temperature to obtain the product.

8. The method for preparing catechol-based resin micro-nanospheres loaded with silver nanoparticles as claimed in claim 7, wherein the silver ammonia solution is prepared by mixing a low concentration ammonia solution with a silver nitrate solution until they are completely dissolved.

9. Use of catechol-based resin micro-nanospheres obtained by the method for preparing catechol-based resin micro-nanospheres according to any one of claims 1 to 4 as carriers of precious metal nanomaterials.

Citation Information

Patent Citations

  • Method for forming ultra-small-size and high-density nano-silver particles through in-situ reduction on surfaces of phenolic resin microspheres under assistance of tannic acid coating

    CN113787194A